2017
DOI: 10.1136/bmjopen-2016-015559
|View full text |Cite
|
Sign up to set email alerts
|

Increased household financial strain, the Great Recession and child health—findings from the UK Millennium Cohort Study

Abstract: BackgroundThere is a growing body of evidence associating financial strain (FS) with poor health but most of this research has been cross-sectional and adult-focused. During the ‘Great Recession’ many UK households experienced increased FS. The primary aim of this study was to determine the impact of increased FS on child health.MethodsWe analysed the Millennium Cohort Study, a longitudinal study of children born in the UK between 2000 and 2002. Surveys at 7 years (T1, 2008) and 11 years (T2, 2012) spanned the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Among a U.S. cohort of female children, James-Todd et al ( 2010 ) found that downward socioeconomic mobility between birth and age seven was associated with a decline in the age at menarche. Similarly, two studies in the U.K. showed that children exposed to negative changes in household income experienced worse physical health overtime (Lai et al 2019 ; McKenna et al 2017 ), particularly compared to children exposed to improvements in household income (Lai et al 2019 ). A relationship between SES changes and asthma was also found in two articles.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Among a U.S. cohort of female children, James-Todd et al ( 2010 ) found that downward socioeconomic mobility between birth and age seven was associated with a decline in the age at menarche. Similarly, two studies in the U.K. showed that children exposed to negative changes in household income experienced worse physical health overtime (Lai et al 2019 ; McKenna et al 2017 ), particularly compared to children exposed to improvements in household income (Lai et al 2019 ). A relationship between SES changes and asthma was also found in two articles.…”
Section: Resultsmentioning
confidence: 96%
“…Among the three studies conducted in Quebec, Canada there was no evidence that household income changes had a unique effect on child/adolescent anthropometric measures not observed among all children exposed to low-income (Côté-Lussier et al 2015 ; Kakinami et al 2014b ; Séguin et al 2007 ). In comparison, two studies in the U.K. and three Brazilian studies showed mixed evidence, with only one study in each country displaying a unique effect of changing income on child/adolescent BMI (Hackenhaar et al 2013 ; Hallal et al 2012 ; Lai et al 2019 ; McKenna et al 2017 ; Muraro et al 2016 ). The results of the eight studies in the U.S. were also contradictory, although the majority (n = 6) found that either short or long-term decreases in household income were associated with increased subsequent BMI among children and adolescents, and similarly increases in household income were associated with lower subsequent BMI-z scores or weight statuses (Balistreri and Van Hook 2011 ; Demment et al 2014 ; Jo 2018 ; Jones 2018 ; Kendzor et al 2012 ; Margerison-Zilko and Cubbin 2013 ; Min et al 2018 ; Oddo and Jones-Smith 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a face-to-face in-hospital survey as part of H2O and collected information on the child's demographic characteristics, including age (<3, 3-10, or >10 years), race (white, African American, or other), and insurer (private or public or self-pay). 2,15 Parents selfreported their own sex, marital status (single, widowed, separated, divorced, or married or living with partner), educational attainment (less than a college degree or college or more), employment status, and work flexibility. We categorized the employment variable according to the number of parents who were employed (0, 1, or 2) and whether that employment was full-or parttime.…”
Section: Data Collectionmentioning
confidence: 99%
“…The financial crash of 2007–2008, the resulting ‘great recession’, and the implementation of a variety of economic policy responses (including implementation of a fiscal stimulus in many countries up until around 2010, and subsequently ‘austerity’19 preceded the current change in mortality rate trends and have been suggested as the direct or indirect causes of the recent trends 1 8 20–22…”
Section: Introductionmentioning
confidence: 99%